The Impact of Blockchain Technology on International Trade and Financial Business - Slatvinska, Valeriia M.; Слатвінська, Валерія Микoлaївна; Слатвінська, В. М.; Demchenko, Vitaliia; Tretiak, Kateryna; Hnatyuk, Rostyslav; Yarema, Oleg (My University, 2022)
This article examines the impact of blockchain technology in the financial sector and international trade. The aim of the article is to measure the effect of blockchain technology on international trade and financial business. The paper uses methods of analysis and synthesis of information from researched academic articles, government programs, reports, and statistical data. The averages and regression analysis (in particular, the calculation of the Pearson coefficient) are used for getting analytical results. Graphic methods are used to summarize the information and to present the understudy materials. According to the results of the study, it can be concluded that blockchain technology has great potential for the development of international trade and financial business. It is possible by improving the settlement of international trade, applying smart contracts in the formation of the transaction, improving logistics chains, and reducing the speed of information and delivery processing, increasing the economic turnover. Blockchain has a positive impact on reducing costs for merchants and the banking sector, predicted by 2030 to decrease costs by 11% using this technology. The technology will have a very significant impact on the development of intellectual property, which could be particularly activated by the possibility of reducing the impact of pirated copying. It is possible to reduce corruption and fraud by applying blockchain technology in public procurement, which currently accounts for the bulk of international trade. Blockchain technology will add $3 trillion in additional business value by 2030 and $866 bln in international trade, including financial business.

У цій статті розглядається вплив технології блокчейн на фінансовий сектор і міжнародну торгівлю. Метою статті є вимірювання впливу технології блокчейн на міжнародну торгівлю та фінансовий бізнес. У роботі використано методи аналізу та узагальнення інформації з досліджуваних наукових статей, державних програм, звітів, статистичних даних. Для отримання аналітичних результатів використовуються середні значення та регресійний аналіз (зокрема, розрахунок коефіцієнта Пірсона). Для узагальнення інформації та подання досліджуваних матеріалів використовуються графічні методи. За результатами дослідження можна зробити висновок, що технологія блокчейн має великий потенціал для розвитку міжнародної торгівлі та фінансового бізнесу. Це можливо за рахунок вдосконалення розрахунків міжнародної торгівлі, застосування смарт-контрактів при формуванні транзакції, вдосконалення логістичних ланцюжків і зниження швидкості обробки інформації та доставки, збільшення економічного обороту. Blockchain має позитивний вплив на зниження витрат торговців і банківського сектору, за прогнозами, до 2030 року вони зменшать витрати на 11% за допомогою цієї технології. Технологія матиме дуже значний вплив на розвиток інтелектуальної власності, яка може бути особливо активована завдяки можливості зменшення впливу піратського копіювання. Зменшити корупцію та шахрайство можна, застосовуючи технологію блокчейн у державних закупівлях, на які зараз припадає основна частина міжнародної торгівлі. Технологія блокчейн додасть 3 трильйони доларів додаткової вартості бізнесу до 2030 року та 866 мільярдів доларів у міжнародній торгівлі, включаючи фінансовий бізнес.
The Impact of Blockchain Technology on International Trade and Financial Business / V. Slatvinska, V. Demchenko, K. Tretiak, R. Hnatyuk, O. Yarema // Universal Journal of Accounting and Finance, 10(1), 2022. - P. 102 - 112. DOI: 10.13189/ujaf.2022.100111.
Keywords: Blockchain; Cryptocurrency; Smart-Contract; International Trade; Financial Business; Intellectual Property; Блокчейн; Криптовалюта; Смарт-контракт; Міжнародна торгівля; Фінансовий бізнес; Research Subject Categories::TECHNOLOGY; Research Subject Categories::SOCIAL SCIENCES::Business and economics